Computational design of Mg alloys with minimal galvanic corrosion - Thekkepat, Krishnamohan; Han, Hyung-Seop; Choi, J.-W.; Lee, Seung Cheol; Yoon, E.S.; GUANGZHE, LI; Seok, Hyun Kwang; Kim, Yu-Chan; Kim, J.-H.; Cha, P.-R. (National Engineering Research Center for Magnesium Alloys of China, Chongqing University, 2022)
Formation of galvanic cells between constituent phases is largely responsible for corrosion in Mg-based alloys. We develop a methodology to calculate the electrochemical potentials of intermetallic compounds and alloys using a simple model based on the Born-Haber cycle. Calculated electrochemical potentials are used to predict and control the formation of galvanic cells and minimize corrosion. We demonstrate the applicability of our model by minimizing galvanic corrosion in Mg-3wt%Sr-xZn alloy by tailoring the Zn composition. The methodology proposed in this work is applicable for any general alloy system and will facilitate efficient design of corrosion resistant alloys. ？ 2021